Endogenous Price Leadership and the Strategic Acquisition of Information. (4th December 2015) - Gilpatric, Scott M.; Li, Youping
Abstract : We model a differentiated Bertrand duopoly in which a firm's earlier knowledge of market demand than its competitor results in endogenous price leadership with the information advantaged firm leading. In such a setting with second‐mover advantage, we then study the firms' incentives to acquire information and analyze an information acquisition game. Both (i) neither firm acquiring information and (ii) one firm acquiring information can arise as subgame perfect equilibrium, but both firms acquiring information is never an equilibrium outcome, even if information is free. Information may have a negative value if it causes a change in the timing of price competition.